Association between hs-CRP Levels and the Outcomes of Patients with Small-Artery Occlusion - Qiu, Ruiying; Gao, Yuan; Hou, Dongzhe; Wang, Yajing; Yu, Changshen; Wang, Wanjun; Liu, Shoufeng; Gao, Chunlin; Tong, Xiaoguang; Wu, Jialing (Frontiers in Aging Neuroscience, 2016)
Background: High-sensitivity C-reactive protein (hs-CRP) is not only a marker of inflammation but also a prognostic factor for ischemic stroke. The objective of our study was to investigative the association between hs-CRP levels and outcomes of patients with small-artery occlusion (SAO). Methods: We selected 718 participants diagnosed with SAO (according to Trial of Org 10172 in Acute Stroke Treatment classification) using the stroke registry of the Department of Neurorehabilitation of Tianjin HuanHu Hospital. Hs-CRP values at admission were classified into 3 categories: < 0.91 mg/L, 0.91 to < 2.77 mg/L, and ≥ 2.77 mg/L. Patients were divided into two subgroups based on age: the younger subgroup (< 75 years) and the elder subgroup (≥ 75 years). Clinical outcomes were evaluated with the modified Rankin scale (mRS) 3 months after the onset of stroke. We examined the relationship between hs-CRP levels at the time of admission and mRS scores using multivariate logistic regression analysis. We also assessed the association between hs-CRP levels and patient outcomes according to age. Results: Among 718 patients with SAO (mean age, 61.7±11.3 years), median hsCRP was 1.54 mg/L. Although 628 patients had a favorable outcome, and 90 patients had a poor outcome at 3 months after SAO. Compared with the lowest levels of hs-CRP, those highest levels of hs-CRP (hsCRP>2.77 mg/L) were at increased risk of poor outcome (adjusted odds ratio, 1.917; 95% CI, 1.050–3.500; P = 0.034), and more than twice the risk of poor outcome among patients in the younger subgroup (adjusted odds ratio, 2.092; 95% CI, 1.079–4.058; P = 0.029). These associations persisted after adjustment for confounding risk factors. However, hs-CRP levels were not significantly associated with outcome among patients in the elder subgroup. Conclusions: Elevated hs-CRP in patients with SAO is an independent predictor of poor prognosis; however, this association is only present in younger patients (< 75 years).